PERAN KESEIMBANGAN PEKERJAAN-KELUARGA DAN KUALITAS HIDUP TERHADAP KEBAHAGIAAN KERJA PADA PETUGAS PEMASYARAKATAN PEREMPUAN - Ratnaningsih, Ika Zenita; Prasetyo, Anggun Resdasari (Jurnal Psikologi, 2019)
Correctional officers encounter vulnerable working conditions that may cause psychological discomfort at work. This study aims to determine the role of work-family balance, and quality of life to happiness at work in female correctional officers. The subjects in this study were 87 female correctional officers from three correctional institutions in Semarang and Malang. The age of subjects ranged from 22 - 57 years (Mage = 41.80); and the work period of the subjects ranged from 3-34 years (Mtenure = 18.80). The sampling technique used was convenience sampling. Instruments that used for data collection were demographic data questionnaires, Work-Family Balance Scale (32 items; Î± = .898), WHOQOL-BREF Scale (26 items; Î± = .906), and Happiness at Work Scale (22 items; Î± = .801). Data analysis using multiple regression analysis show there a positive and significant correlation between work-family balance and happiness at work (r = .613; p <.001), there was a positive and significant correlation between quality of life and work happiness (r = .394; p <.001), furthermore work-family balance and quality of life together can predict happiness at work in female correctional officers (r = .633; R2 = .401; F = 28.115; p <.001). Work-family balance and quality of life effectively contributed 39.7%Â  to predicting happiness at work in female correctional officers.